The Role of Mitophagy in Ischemic Stroke - Shao, Ziqi; Dou, Shanshan; Zhu, Junge; Wang, Huiqing; Xu, Dandan; Wang, Chunmei; Cheng, Baohua; Bai, Bo (Frontiers in Neurology, 2020)
Mitochondria are an important place for eukaryotes to carry out energy metabolism and participate in the processes of cell differentiation, cell information transmission and cell apoptosis. Autophagy is a programmed intracellular degradation process. Mitophagy, as a selective autophagy, is an evolutionarily conserved cellular process to eliminate dysfunctional or redundant mitochondria, thereby fine-tuning the number of mitochondria and maintaining energy metabolism. Many stimuli could activate mitophagy, activate signal pathways, regulate related physiological processes, and ultimately reduce or aggravate the damage caused by stimulation. In recent years, stroke has become a major disease that seriously endangers the health and lives of global residents. However, ischemic stroke caused by cerebral vascular stenosis or obstruction and insufficient blood supply to the brain accounts for the vast majority of stroke. Abnormal mitophagy is closely related to the occurrence, development and pathological mechanism of ischemic stroke. However, the exact mechanism of mitophagy involved in ischemic stroke and its underlying molecular mechanism have not been fully elucidated. This review details the process and signal pathways of mitophagy, and understands the potential role of mitophagy in ischemic stroke and possible signal transduction pathways. It will help deepen the understanding of mitophagy and provide new ideas for the treatment of ischemic stroke.